Analysis of the Current Status and Influencing Factors of Life Satisfaction among Middle-Aged and Elderly Patients with Chronic Diseases - ZHU Guochen; CHEN Zhuoming (康复学报, 2025)
ObjectiveThis study used the 2020 China health and retirement longitudinal study (CHARLS) data to explore the current status and influencing factors of life satisfaction among middle-aged and elderly patients with chronic diseases aged 45 and above in China, in order to provide scientific basis for health management and reveal potential paths to improve their life satisfaction.MethodsThe latest 2020 wave 5 national survey data released by CHARLS was used, and 13 487 middle-aged and elderly patients with chronic diseases over 45 years old were selected as the research subjects. Chronic disease data were collected using the question with the original questionnaire code da007; gender, age, education level, place of residence, living with a partner, number of chronic diseases, child satisfaction, number of social activities, smoking, alcohol consumption, pension insurance, medical insurance, basic activities of daily living (BADL), instrumental activities of daily living (IADL), nighttime sleep duration, and midday sleep duration were included as demographic variables. The life satisfaction of middle-aged and elderly patients with chronic diseases was collected using the original questionnaire code dc026.ResultsA total of 13 487 patients with chronic diseases were included. There were significant differences in life satisfaction among middle-aged and elderly patients with chronic diseases in the following aspects: gender, age, education level, place of residence, whether living with partners, number of chronic diseases, child satisfaction, alcohol consumption, whether having pension insurance, whether having medical insurance, BADL impairment, IADL impairment, nighttime sleep duration and midday sleep duration (P<0.05). There were no statistically significant differences in the number of social activities and whether smoking (P>0.05). Middle aged and elderly patients with chronic diseases suffered from a wide range of chronic diseases, with a probability over 50% for hypertension, stomach or other digestive system diseases. There were 3 914 middle-aged and elderly patients with one chronic disease, 3 445 patients with two chronic diseases, 2 468 patients with three chronic diseases, and 3 660 patients with four or more chronic diseases. A total of 1 232 patients were dissatisfied with their lives, and 12 255 patients were satisfied. The results of binary logistic regression analysis showed that age range of 55-64 years (95%CI=0.49-0.77), 65-74 years (95%CI=0.37-0.59), 75-84 years (95%CI=0.28-0.46), and 85 years and above (95%CI=0.19-0.41), with a nighttime sleep duration of 6-8 hours (95%CI=0.72-0.95) and ≥8 h (95%CI=0.62-0.88), and a midday sleep duration of 1-2 hours (95%CI=0.65-0.86) and ≥2 h (95%CI=0.56-0.86) were protective factors for life satisfaction among middle-aged and elderly patients with chronic diseases (P<0.05); Living in rural areas (95%CI=0.65-0.89), not living with a partner (95%CI=1.39-1.81), having four or more chronic diseases (95%CI=1.17-1.64), being dissatisfied with children (95%CI=3.27-4.66), not having medical insurance (95%CI=1.22-2.04), impaired BADL (95%CI=1.20-1.62), and impaired IADL (95%CI=1.26-1.70) were risk factors for life satisfaction among middle-aged and elderly patients with chronic diseases (P<0.05).ConclusionMiddle aged and elderly patients with chronic diseases in China have a high overall satisfaction with their lives. It is necessary from the perspective of family environment and social support to create a good family atmosphere, improve the medical security system, strengthen monitoring and intervention of mental health, and strive for the physical and mental health of middle-aged and elderly patients with chronic disease.